2017
DOI: 10.2337/db17-0132
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Neuropilin 1 in Myeloid Cells Exacerbates High-Fat Diet–Induced Insulin Resistance Through Nlrp3 Inflammasome In Vivo

Abstract: Neuropilin 1 (Nrp1), a coreceptor for class 3 semaphorins and growth factors, is highly expressed in vascular cells and myeloid cells, including macrophages. Unlike well-characterized proangiogenic functions of endothelial cell Nrp1, the contributions of macrophage Nrp1 within the context of metabolic dysfunction remain to be established. The aim of this study was to determine the contributions of macrophage Nrp1 in high-fat diet (HFD)-instigated insulin resistance in vivo. Insulin sensitivity and Nlrp3 inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…A subset of neuropilin‐1 (NRP1) expressing ATMs has recently been found to protect against obesity . Myeloid cell‐specific Nrp1 deficiency (Nrp1 myel−KO mice) activates the NLRP3 inflammasome, which increases the synthesis of inflammatory IL‐1β and IL‐18 cytokines in macrophages . Additionally, inflammasome activation and subsequent IR do not occur in the AT of HFD‐fed Nlrp3 −/− mice that indicate the importance of the pathway in the induction of IR .…”
Section: White Adipose Tissue (Wat) In Health and Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…A subset of neuropilin‐1 (NRP1) expressing ATMs has recently been found to protect against obesity . Myeloid cell‐specific Nrp1 deficiency (Nrp1 myel−KO mice) activates the NLRP3 inflammasome, which increases the synthesis of inflammatory IL‐1β and IL‐18 cytokines in macrophages . Additionally, inflammasome activation and subsequent IR do not occur in the AT of HFD‐fed Nlrp3 −/− mice that indicate the importance of the pathway in the induction of IR .…”
Section: White Adipose Tissue (Wat) In Health and Obesitymentioning
confidence: 99%
“…92 Myeloid cell-specific Nrp1 deficiency (Nrp1 myel−KO mice) activates the NLRP3 inflammasome, which increases the synthesis of inflammatory IL-1β and IL-18 cytokines in macrophages. 93,94 Additionally, inflammasome activation and subsequent IR do not occur in the AT of HFD-fed Nlrp3 −/− mice that indicate the importance of the pathway in the induction of IR. 93 After HFD in mice, Th1 cytokines (IFN-γ, TNF-ɑ and granulocytemacrophage colony-stimulating factor [GM-CSF]) induce the generation of classically activated pro-inflammatory CD11c + M1-like macrophages within the AT that contributes to the induction of IR.…”
Section: Monocytes and Macrophagesmentioning
confidence: 99%
“…With respect to how Nrp1 ablation exacerbates insulin resistance in vivo, a number of important findings are noteworthy. Firstly, we observed that systemic inflammation significantly increased in HFD-fed Nrp1 myel-KO mice [6] . Secondly, Nrp1 myel-KO mice displayed aberrant activation of Nlrp3 inflammasome, as evidenced by elevated levels of Nlrp3, cleaved caspase 1 p20, pro-IL-1β, IL-1β p17, or IL-18 [6] .…”
mentioning
confidence: 90%
“…In our recently published article, we provided first evidence of a direct link between Nrp1 and obesity. HFD-fed obese mice exhibited decreased Nrp1 expression in macrophages rather than other detected cells [6] . In addition, by generating myeloid cell-specific Nrp1 deficient (Nrp1 myel-KO ) mice, we demonstrated that Nrp1 deficiency exacerbated insulin resistance upon HFD relative to wild-type, control mice group [6] .…”
mentioning
confidence: 97%
See 1 more Smart Citation